2017
DOI: 10.3389/fimmu.2017.00985
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Intestinal Inflammation Is Suppressed by Catestatin in a Murine Model of Colitis via M1 Macrophages and Not the Gut Microbiota

Abstract: While there is growing awareness of a relationship between chromogranin-A (CHGA) and susceptibility to inflammatory conditions, the role of human catestatin [(hCTS); CHGA352-67] in the natural history of established inflammatory bowel disease is not known. Recently, using two different experimental models, we demonstrated that hCTStreated mice develop less severe acute colitis. We have also shown the implication of the macrophages in this effect. The aims of this study were to determine (1) whether hCTS treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 109 publications
4
54
0
2
Order By: Relevance
“…To the best of our knowledge, only one study thus far has measured serum CST levels in a small sample of IBD patients. However, serum CST concentrations were not their primary outcome and other relevant clinical information, as well as biochemical parameters are lacking in that study [31]. Therefore, we believe that this study is the first clinical study to investigate serum CST levels in the IBD population and control subjects with detailed relevance to disease characteristics.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…To the best of our knowledge, only one study thus far has measured serum CST levels in a small sample of IBD patients. However, serum CST concentrations were not their primary outcome and other relevant clinical information, as well as biochemical parameters are lacking in that study [31]. Therefore, we believe that this study is the first clinical study to investigate serum CST levels in the IBD population and control subjects with detailed relevance to disease characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…Intestinal inflammation has been associated with dysfunctional ChgA production [28]. Consequently, several experimental studies on animal colitis model investigated the relationship of intestinal inflammation and CST secretion [29][30][31][32]. Rabbi et al evaluated the impact of CST on intestinal microbiota in mice and revealed significant changes that could potentially lead to development of new options in treating IBD patients [29].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Murine models of colitis are key tools used to investigate the pathophysiology of intestinal inflammation (Auletta et al, ; Rabbi et al, ). Dextran sodium sulfate (DSS)‐induced colitis is the most common animal model of IBD used with over 4,000 entries in PubMed (Eissa et al, ); therefore, DSS‐induced colitis was used in this study (PubMed, RRID:SCR_004846).…”
Section: Methodsmentioning
confidence: 99%